Implementation of Bruner’s Representation Approach in Financial and Accounting Learning - Wiraning Furi, Nurul Senja; Wiradinata, Rochanda; Curatman, Aang (Annpublisher, 2025)
Background. Financial literacy is a fundamental aspect of making smart economic decisions. In an era of increasing global economic complexity, a thorough understanding of fundamental financial and accounting principles is crucial for individuals to manage assets effectively and maximize profits. Aims. Analyze Bruner's cognitive learning theory from relevant literature studies and describe the implications of Bruner's cognitive learning theory in financial and accounting learning models. Methods. This study employs a qualitative approach, integrating case studies and data analysis to examine how Bruner’s representation theory can be effectively implemented in financial literacy and accounting education. Result. Bruner's theory provides a systematic approach to learning through representational stages, comprising enactive, iconic, and symbolic representations. Applying this theory in financial literacy and accounting education enables learners to grasp financial concepts progressively, thereby enhancing conceptual understanding and practical application. Conclusion. This article examines the implementation of Bruner's representations in financial and accounting education, exploring their impact on enhancing financial literacy, particularly in making more effective and sustainable economic decisions